The Potential Diagnostic Accuracy of Autopsy Lung Weights, Lung-Heart Ratio, and Lung-Body Ratio in Drowning Deaths. (September 2018) - Tse, Rexson; Garland, Jack; Kesha, Kilak; Morrow, Paul; Lam, Leo; Elstub, Hannah; Cala, Allan; Spark, Amy; Palmiere, Cristian; Stables, Simon
Abstract : Abstract: Lung weights are often increased in drowning deaths as well as in other types of deaths. Lung weights may also vary with age, sex, and body weight. A variety of methods have been proposed to utilize lung weight data to assist with the diagnosis of drowning. The present study compared lung weight, lung-heart ratio (LH), and lung-body ratio (LB) between 50 consecutive drowning and 50 nonimmersion deaths in order to assess the accuracy in diagnosing drowning. Analysis revealed both LH and LB to be statistically higher in drowning deaths ( P < 0.05), with LB being the most robust measurement. However, the overall diagnostic accuracies of lung weight, LH, and LB were poor to fair, and should therefore be used only in conjunction with the other diagnostic criteria. Abstract : Supplemental digital content is available in the text.